PENGARUH SENAM HAMIL TERHADAP NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS CAWAS II KABUPATEN KLATEN - Susilowati, Dewi; Istikhomah, Henik; Setiyaningsih, Rini (Jurnal Kebidanan, 2024)
Abstract Third trimester pregnant women will experience physiological changes. One of them is back pain. Untreated back pain will cause discomfort and interfere with daily activities. Interventions that can be given to third trimester pregnant women are pharmacological and non-pharmacological. Pharmacologically, the therapy given uses non-narcotic analgesic and narcotic analgesic drugs. While non-pharmacological therapies include massage, aromatherapy, acupuncture, reflexology, rest, and light exercise (walking, swimming, pilates, and pregnancy exercise. This research to determine the effect of pregnancy exercise on reducing lower back pain in pregnant women at the Cawas II Klaten Health Center. This type of research is a Quasi Experimental study with a One Group Pretest Posttest research design. The researcher measured lower back pain before (pre) pregnancy exercise treatment was carried out on the group of pregnant women, then the group of pregnant women was given pregnancy exercise treatment (treatment) and after being given pregnancy exercise, the group of pregnant women was measured for lower back pain (post) and so on until the lower back pain disappeared. The research design used a quasi-experimental one group pretest-posttest parallel. The scale of lower back pain before pregnancy from 28 respondents before prenatal exercise was on average the lowest on day-1, which was 3.43 with a minimum pain scale of 2 and a maximum of 6. While the scale of lower back pain before prenatal exercise was on average the lowest on day-6, which was 0.07 with a minimum pain scale of 0 and a maximum of 1. The scale of lower back pain from 28 pregnant women after prenatal exercise was the highest on day-1, which was 3.00 with a minimum scale of 1 and a maximum of 5. The scale of lower back pain after prenatal exercise was the lowest on day-6, which was 0.00 with a minimum and maximum scale of 0. It can be interpreted that from 28 pregnant women on day-6 the pain scale disappeared because the pain scale was known to be 0 (zero). Keyword: Pregnancy Exercise, Third Trimester Pregnant Women, Lower Back Pain